2023
DOI: 10.1088/1757-899x/1293/1/012027
|View full text |Cite|
|
Sign up to set email alerts
|

Life cycle assessment of wind turbine blade recycling approaches in the United States

Evan Sproul,
Michelle Williams,
Mitchell L. Rencheck
et al.

Abstract: Most wind turbine blades reaching end-of-life are sent to landfill where embedded cost, energy, and materials are lost. To avoid landfilling future blades, a broad range of recycling and material recovery approaches have been proposed as solutions in the U.S., each with benefits, challenges, and varying levels of technical maturity. The approaches include 1) cement co-processing, 2) mechanical recycling, 3) pyrolysis, 4) microwave pyrolysis and 5) solvolysis. While these approaches are all capable of recoverin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…This study has shown that mechanical recycling could be a low-carbon solution to mixed GRP waste streams, including wind blade waste. This is in close agreement with other studies that investigated the impact of GRP mechanical recycling in North America [13] and China [14]. Unlike FBR, which utilises all the waste GRP mass, the "coarse" fraction remains following the classification stage of mechanical recycling.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study has shown that mechanical recycling could be a low-carbon solution to mixed GRP waste streams, including wind blade waste. This is in close agreement with other studies that investigated the impact of GRP mechanical recycling in North America [13] and China [14]. Unlike FBR, which utilises all the waste GRP mass, the "coarse" fraction remains following the classification stage of mechanical recycling.…”
Section: Discussionsupporting
confidence: 91%
“…This work has shown, however, that while using GRP as feedstock in EfW facilities can reduce landfill burden, this results in significantly higher GWP than simply landfilling. This has also been shown to be the case in North America [13] and China [14]. Given the UK (and other global) commitments to Net Zero 2050, incinerating GRP waste for energy alone must also be avoided.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over recent years, numerous researchers have assessed the carbon footprint associated with different end-of-life (EoL) strategies for GFRP wind blade structures. Sproul et al conducted a comparative LCA to evaluate GHG emissions and material yields across various wind turbine blade recycling methods (including cement co-processing, mechanical, pyrolysis, microwave pyrolysis, and solvolysis recycling) in the United States [22]. They found that both mechanical recycling and microwave pyrolysis yield the lowest net GHG emissions.…”
Section: Introductionmentioning
confidence: 99%